Corrosion Inhibition Efficiency Of Nicotine Based On Quantum Chemical Study - Yayuk Wirayani; Maria Ulfa; Yahmin Yahmin (Acta Chimica Asiana, 2018)
The effect of substituents, electron donor groups (NH2, OH, CH2OH and CH3) and electron withdrawal groups (NO2, COOH, and Cl), to the efficiency of corrosion inhibition of nicotine has been studied using theoretical studies. The effect of substituents toward the efficiency of corrosion inhibition of nicotine based on quantum parameters (EHOMO, ELUMO, Egap, I, Ï‡, dan Î”N). The efficiency of corrosion inhibition based on quantum parameters is NH2 > OH > CH2OH > CH3 > BN > Cl > COOH > NO2. The addition of electron donor group NH2 has the highest inhibitory efficiency of 99.79 %. In contrast, the presence of electron withdrawal group NO2 has the opposite effect.